2012
DOI: 10.1007/s00134-011-2454-3
|View full text |Cite
|
Sign up to set email alerts
|

Bedside prediction rule for infections after pediatric cardiac surgery

Abstract: PurposeInfections after pediatric cardiac surgery are a common complication, occurring in up to 30% of cases. The purpose of this study was to develop a bedside prediction rule to estimate the risk of a postoperative infection.MethodsAll consecutive pediatric cardiac surgery procedures between April 2006 and May 2009 were retrospectively analyzed. The primary outcome variable was any postoperative infection, as defined by the Center of Disease Control (2008). All variables known to the clinician at the bedside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
1
22
1
8
Order By: Relevance
“…La edad del paciente menor a 6 meses, estadía mayor a 48 h en UPC-P y esternón abierto por más de 48 horas fueron considerados por Alegra y cols., como factores predictores para un mayor riesgo de infección 1 . La estadía prolongada está comúnmente asociada con mayor duración de la ventilación mecánica y aumento en el tiempo de uso de catéteres intravasculares [25][26][27][28] .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La edad del paciente menor a 6 meses, estadía mayor a 48 h en UPC-P y esternón abierto por más de 48 horas fueron considerados por Alegra y cols., como factores predictores para un mayor riesgo de infección 1 . La estadía prolongada está comúnmente asociada con mayor duración de la ventilación mecánica y aumento en el tiempo de uso de catéteres intravasculares [25][26][27][28] .…”
Section: Discussionunclassified
“…Se han reportado incidencias que van de 16 a 31%, más alta que la observada en los pacientes hospitalizados en unidades de cuidados intensivos pediátricos general. Está ampliamente reportada su asociación con aumento en los días de hospitalización, costos asociados a la intervención, uso de antimicrobianos y riesgo de mortalidad [1][2][3][4][5][6][7][8] . Los tipos más comunes de IAAS reportadas en pacientes pediátricos post operados de cirugía cardíaca son las infecciones del sitio quirúrgico y del torrente sanguíneo.…”
unclassified
See 1 more Smart Citation
“…Infection in children post-congenital heart surgery is a frequent complication, with a reported incidence as high as 30 % (Pollock et al 1990;Pasquali et al 2013;Ben-Ami et al 2008;Algra et al 2012). Some of the infections are superficial surgical wound infections.…”
Section: Infectious Diseasementioning
confidence: 99%
“…Multiple groups have studied risk factors associated with developing an infection post-pediatric cardiac surgery. Algra et al identified age less than six months, a post-operative ICU stay longer than 48 hours, and an open sternum for more than 48 hours as risk factors for infection (Algra et al 2012). Costello et al identified age younger than one year and longer cardiopulmonary bypass duration as independent risk factors for infection post-cardiac surgery (Costello et al 2010).…”
Section: Infectious Diseasementioning
confidence: 99%